IL-6 and IL-10 Are Associated With Gram-Negative and Gram-Positive Bacteria Infection in Lymphoma - Zhu, Qiuhua; Li, Huan; Zheng, Shanshan; Wang, Bin; Li, Mingjie; Zeng, Wenbin; Zhou, Lanlan; Guan, Zebing; Wang, Hong; Liu, Yanan; Gao, Yanmin; Qiu, Shiqiu; et al. (Frontiers in Immunology, 2022)
To investigate the Th1/Th2 cytokine profile in patients with lymphoma during the myelosuppression stage of infection. 52 patients with gram-negative bacterial infection (G- group), 49 patients with gram-positive bacterial infection (G+ group), 51 uninfected patients with lymphoma (uninfected group) and 20 healthy controls (healthy group) were enrolled in this study. We evaluated the quantification of Th1/Th2 cytokines with flow cytometry bead assay (CBA) in the sera to explore a rapid diagnostic method to determine the type of infection and anti-infective effect. The levels of procalcitonin (PCT) were also detected simultaneously. The four groups did not differ with regard to IL-2 and IL-4 (P>0.05). The IFN-γ and TNF-α levels of patients with lymphoma were higher than those of healthy controls (P<0.05). There was significantly upregulated IL-6 and IL-10 expression in the G- group (P<0.001). A similar trend was reflected in the IL-6 of the G+ group, which was significantly increased (P<0.001). However, no significant upregulation was observed for IL-10 in the G+ group. According to the different degrees of increased IL-6 and IL-10 levels, We proposed to use the G- Bacterial Infection Cytokine Profile (G- BICP) and the G+ Bacterial Infection Cytokine Profile (G+ BICP) for the first time to differentiate between Gram-negative and Gram-positive (G-/G+) bacterial infection in adults with lymphoma in the myelosuppression stage after chemotherapy. The IL-6, IL-10 and PCT in the G- group and the IL-6, PCT in the G+ group were significantly decreased at day 4 and day 8 compared with those at day 1. IL-6 and IL-10 are closely associated with the severity and treatment efficacy in adults with lymphomas who develop infections after chemotherapy and can help distinguish between G- and G+ bacterial infections at an early stage.